The power of dyslexia an advocacy campaign in reinforcing dyslexia awareness towards Filipino middle class parents, ages 25-35, in Quezon City - Lladoc, Gabrielle A.
Children with Dyslexia trouble reading, writing, and spelling, because they process information differently. Less than 1% of Filipino children with Dyslexia are diagnosed and provided with special education services because their parents are not well-informed about Dyslexia. Through showing that having the right knowledge and endless support can help reduce a child's academic failure, this research highlights the importance of high-level awareness on Dyslexia and its positive effects in children with Dyslexia. The Power of Dyslexia is an advocacy campaign that reinforces Dyslexia awareness towards Filipino Parents by informing them about Dyslexia and strategies on how to accommodate and support their children. The campaign promotes a supportive and well-informed environment and empowers parents and their children with Dyslexia that they can excel despite having difficulties if given the attention and support they need.